Primary risk assessment of microplastic pollution in spineless cuttlefish (Sepiella inermis) from the North-East Bay of Bengal: A tissue-based analysis - Sourav Bar; Soumik Dhara; Jhumpa Majhi; Dipak Bisai; Edris Alam; Md Kamrul Islam; Uday Chatterjee; Sudipta Kumar Ghorai (Heliyon, 2024)
Microplastic pollution has a significant threat to marine ecosystems, yet its impact on spineless cuttlefish (Sepiella inermis) remains under-researched. This study aims to address this gap by analysing microplastic contamination in Sepiella inermis from the North-East Bay of Bengal. This species is widely consumed and transported globally as food, thus holding significant health concerns. A total of 40 adult female cuttlefish were collected from two sampling sites (18°36′31.35″N 87°48′10.63″E and 15°43′35.37″N 88°12′07.01″E) in the Bay of Bengal. Tissue samples from tentacles, gut, and nidamental glands were analysed for microplastic content, alongside sediment and surface water samples. Parameters such as microplastic abundance, size, shape, and colour were recorded. The average abundance of microplastic particles was measured at 2.003 particles per gram in tentacle tissue, 2.31 particles per gram in gut tissue, and 0.99 particles per gram in nidamental gland tissue. The gut tissue exhibited the highest abundance of microplastics per gram. Chemical characterization using FT-IR and confocal Raman spectroscopy identified 11 types of microplastic polymers. Of the 11 types of plastic polymers identified, PVC was the most prevalent, accounting for 17.64 % of the microplastics found across all tissues. PVC microplastics can cause significant harm to marine life and human health by accumulating in the food chain and releasing harmful chemicals like phthalates, which can lead to endocrine disruption. ABS, PET, PP, PE, and PA microplastic polymers are highly persistent in environment, leading to long-term pollution in oceans. When ingested by marine organisms, they can disrupt entire ecosystems. In humans, the accumulation of these microplastics can impair the immune system and contribute to chronic diseases. The Pollution Load Index (PLI) was calculated for each tissue type, revealing that gut tissue is more prone to microplastic pollution compared to the nidamental gland and tentacles. The average PLI per gram of gut tissue was 2.26, which was significantly higher than 1, indicating substantial pollution. This research highlights the urgent need for comprehensive strategies to mitigate microplastic pollution, given the potential health risks associated with the consumption of contaminated marine species.